ANALISIS PENGGUNAAN TWIN BLOCK PADA PERAWATAN MALOKLUSI DENTOSKELETAL KELAS II DIVISI 1 DISERTAI RETROGNATI MANDIBULA BERDASARKAN CERVICAL VERTEBRAL MATURATION STAGE - Deta Putri Futuhat, Arlette Suzie P, Meirina Gartika (Universitas Islam Sultan Agung, 2018)
Background:Class II division 1 dentoskeletal malocclusion with mandibular retrognatic can be treated with twin block appliance. The objectives of this study are to analyse twin block appliance based on mandibular dimension and anterior facial height changes, and to determined the most effective time base on CVMS to begin the treatment. Method: The type of research was a retrospective analysis study using secondary data. The sample was 14 lateral cephalometric radiographs before and after treatment with twin block appliance. It was taken in IKGA RSGM FKG UNPAD 2010 to 2016. Statistic analysis used paired t-test. Results: Study shows that there is a significant change (p<0.05) in mandibular dimension and anterior facial height after treatment with twin block appliance. Changes in mandibular dimension including total mandibular length, mandibular body length, ramus height, and gonial angle. Changes in anterior facial height including lower anterior facial height and total anterior facial height. The CVMS III group showed statistically significant result with the biggest improvement. Conclusion: The use of twin block appliance in Class II division 1 dentoskeletal malocclusion with mandibular retrognatic could change mandibular dimension and anterior facial height. Apart from that, CVMS III was found to be the most effective time to start the treatment with twin block appliance